Application of periodic regression analysis on reported cases of dengue hemorrhagic fever in the City of Manila 1963-1982 - Leano, Fe T.
This study intends to determine the existence of cyclical and secular trends of dengue hemorrhagic fever cases in the City of Manila for a 20-year period, 1963 to 1982. Data for this study were attained from the Manila Health Department and the incidence rates were subsequently computed. Findings revealed that the computed maximum DHF incidence was mid-October while the minimum was 6 months later, mid-April; and the vector density and climatological differences per year may have triggered the significant variation in amplitude and phase angle from year to year.